Effectiveness of advisory warnings based on cooperative perception. Issue 6 (1st August 2015) - Naujoks, Frederik; Grattenthaler, Heidi; Neukum, Alexandra; Weidl, Galia; Petrich, Dominik
Abstract : Cooperative perception makes it possible to provide drivers with early advisory warnings about potentially dangerous driving situations. On the basis of the research results pertaining to imminent crash warnings, it was expected that the effectiveness of such advisory warnings depends on situation‐specific anticipations by the driver. During a simulator study, N = 20 drivers went through a wide range of longitudinal traffic and intersection scenarios. The scenarios varied in the possibility to anticipate traffic conflicts (anticipation: high against low) and were completed under different visibility conditions (visibility: obstructed against visible), with and without driver assistance based on cooperative perception (i.e. visual–auditory advisory warnings 2 s prior to the last‐possible warning moment; assistance: no assistance against with assistance). The warning concept was based on empirical pre‐studies and previously validated on a public test intersection. During non‐assisted driving, critical situations were mainly experienced when the possibility to anticipate traffic conflicts was low. Visual obstructions lead to a further increase in the frequency of critical situations. Furthermore, the results indicate a clear mitigation of critical encounters when providing early advisory warnings. This applies particularly to surprising and unexpected scenarios and thus illustrates the potential of cooperative perception to enhance active traffic safety.